2019
DOI: 10.3390/pharmaceutics11120652
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Intracellular Delivery of BCG Cell Wall Skeleton into Bladder Cancer Cells Using Liposomes Functionalized with Folic Acid and Pep-1 Peptide

Abstract: Although bacillus Calmette–Guérin cell wall skeleton (BCG-CWS) might function as a potential substitute for live BCG, its use in the treatment of bladder cancer remains limited owing to issues such as insolubility and micrometer-size following exposure to an aqueous environment. Thus, to develop a novel nanoparticulate system for efficient BCG-CWS delivery, liposomal encapsulation was carried out using a modified emulsification-solvent evaporation method (targets: Size, <200 nm; encapsulation efficiency, ~6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Several options have been explored to enhance the permeability, pharmacokinetics, and targeted selectivity across the buccal membrane. Accordingly, permeation enhancers, adhesive polymers, prodrugs, lipid-based nanocarriers, polymer-based nanocarriers, and hybrid nanocarriers have been designed [5][6][7][8][9][10]. Among these, lipid-based nanocarriers, particularly liposomes that are composed of natural or synthetic phospholipids, with or without cholesterol, have shown tremendous potential in increasing the permeability and bioavailability of peptide drugs [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Several options have been explored to enhance the permeability, pharmacokinetics, and targeted selectivity across the buccal membrane. Accordingly, permeation enhancers, adhesive polymers, prodrugs, lipid-based nanocarriers, polymer-based nanocarriers, and hybrid nanocarriers have been designed [5][6][7][8][9][10]. Among these, lipid-based nanocarriers, particularly liposomes that are composed of natural or synthetic phospholipids, with or without cholesterol, have shown tremendous potential in increasing the permeability and bioavailability of peptide drugs [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, in this study, we developed an improved system for the intravesical delivery of BCG-CWS in an orthotopic tumor mouse model of bladder cancer. Previously, we performed flow cytometry and a confocal laser scanning microscopy assay to evaluate the cellular uptake of CWS-Nano-CL in 5637 and MBT2 cells [12]. We showed that the fluorescence peak shift (MFI) value was 34.95 according to flow cytometry, and a strong fluorescence was visualized by confocal laser scanning microscopy (CLSM) for 2 h. As for the results, the cellular uptake of CWS-Nano-CL in MBT2 cells was clearly demonstrated, indicating internalized fluorescence within the cytoplasm for 2 h. To observe the in vivo antitumor efficacies, MBT2-Luc cells were instilled into the bladders of C3H/HeN mice.…”
Section: Discussionmentioning
confidence: 99%
“…Although BCG-CWS is a potent candidate non-infectious immunotherapeutic drug that could serve as an alternative to live BCG [6,8,9], its aggregation in both aqueous and non-aqueous solvents limits its efficient use in anticancer therapy. To overcome this issue of insolubility and improve the internalization of BCG-CWS into bladder cancer cells, we encapsulated it within a liposomal nanoparticle using an emulsification-solvent evaporation method [12,35]. We showed that, in vitro, though both CWS and CWS-Nano-CL showed antitumor effects on bladder cancer cells, the latter displayed greater efficiency than the former.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations